6th International Symposium on Therapeutic Ultrasound : Oxford U.K., 30 August - 2 September 2006 - International Symposium on Therapeutic Ultrasound (6th : 2006 : Oxford, England); Coussios, Constantin-C.; Haar, G. ter (Gail); International Society for Therapeutic Ultrasound (Melville, NY : American Institute of Physics, 2007)
42